Економічна безпека і роль колективного Заходу у поствоєнному відновленні України - Яковюк, І. В.; Єфремова, К. В.; Новіков, Є. А. (НДІ правового забезпечення інноваційного розвитку НАПрН України; Право, 2022)
Хоча результат російсько-української війни невизначений, необхідно почати думати про майбутню відбудову України. У статті досліджені питання, що стосуються комплексу проблем, пов’язаних з післявоєнним відновленням України і участю в ньому колективного Заходу, під яким розуміють сукупність країн (США, держави-члени ЄС, Канада, скандинавські країни), що беруть участь у євроатлантичній інтеграції. У статті ми спираємося на аналіз попереднього досвіду післявоєнної відбудови Західної Європи (наприклад, план Маршалла після Другої світової війни). Нами викладено ключові принципи міжнародного співробітництва з реконструкції української економіки і держави в цілому, а також роль окремих суб’єктів міжнародного права у цьому процесі. Обговорюється питання про те, наскільки іноземна підтримка має надаватися у вигляді пільгових кредитів (кредити з нижчою відсотковою ставкою, ніж ринкова) або грантів (фінансові трансферти без очікування повернення). Обґрунтовується висновок про те, що гранти мають становити велику частку потоків закордонної допомоги у повоєнній реконструкції України. Важливим кроком у поствоєнному відновленні України має стати списання зарубіжними фінансовими установами, насамперед МВФ та ВБ, зовнішнього боргу або принаймні його частини як важливої та необхідної ознаки справжньої солідарності міжнародної спільноти. Наголошується на особливій ролі США і Європейського Союзу у повоєнній відбудові України, зокрема в питанні списання зовнішнього боргу України. Стаття покликана залучити загал зарубіжних і вітчизняних правників до дискусії з більш широкого кола питань, яка охопить подальший і детальніший аналіз того, як найкраще відновити Україну після завершення війни. Problem setting. Although the outcome of the Russian-Ukrainian war is uncertain, it is necessary to start thinking about the future reconstruction of Ukraine. The paper examines issues related with the complex of problems connected with the post-war reconstruction of Ukraine and the participation of the collective West, which means a set of countries (USA, EU member states, Canada, Scandinavian countries) participating in Euro-Atlantic integration. In this article, we use previous experience of post-war reconstruction of Western Europe (for example, the Marshall Plan after World War II). We set out the key principles of international cooperation in the renovation of the Ukrainian economics and the state as a whole, as well as the role of individual subjects of international law in this process. The paper is intended to involve foreign and domestic lawyers in a discussion on a wider range of issues, which will include further and more detailed analysis of the best ways to rebuild Ukraine after the war. Analysis of resent researches and publications. The idea of developing a European plan for the reconstruction of Ukraine (“Marshall Plan for Ukraine”) began to be discussed after the Revolution of Dignity. However, it has not been the subject of serious research. The situation changed after Russia declared war on Ukraine. As Ukraine has a chance to win the war, the leaders of the United States, the European Union and Ukraine are discussing the possible content of a “New European Plan for Ukraine.” However, today, both in Ukraine and abroad, this issue is dominated by journalistic publications, which determines the relevance and practical significance of the development of the problem. Target of research is to reveal the content, main directions of participation of international financial institutions and individual states in the reconstruction of Ukraine after the war. Article’s main body. The article considers the problem of determining the content of the “New European Plan for Ukraine” in relation to the postwar period. The uniqueness of the plan to restore the Ukrainian economy is emphasized. The steps of international financial institutions and individual countries regarding the revival of Ukraine during and after the war are analyzed. Conclusions and prospects for the development. The conclusion that grants should make up a large share of foreign aid flows in the post-war reconstruction of Ukraine is substantiated. An important step in Ukraine’s post-war reconstruction should be the write-off of foreign debt, or at least part of it, by foreign financial institutions, primarily the IMF and the World Bank, as an important and necessary sign of genuine solidarity of the international community. Emphasis is placed on the special role of the United States and the European Union in the postwar reconstruction of Ukraine, in particular on the issue of writing off Ukraine’s foreign debt.
Keywords: економічна безпека; економічне відновлення; ЄС; колективний Захід; план Маршала; трастовий фонд; Україна; economic security; economic renovation; EU; collective West; Marshall Plan; trust fund; Ukraine